2009
DOI: 10.1111/j.1601-5037.2008.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the relationship between periodontitis, cardiovascular disease and serum lipid levels

Abstract: The results revealed no significant difference with respect to the lipid profile levels between the four groups. Interpreting the results of the study, periodontal disease did not cause an increase in total CHL, LDL or triglyceride levels or a decrease in the HDL levels in an otherwise systemically healthy individual or in a CHD patient. Periodontitis in a CHD patient did not seem to exacerbate the destruction of periodontal tissue. Higher triglyceride levels did not have any correlation with the severity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…HolmPedersen et al [9] investigated the correlations among dental caries, periodontal disease, and cardiac arrhythmia in community-dwelling elderly individuals who were aged 80 or older and showed that there was no association between periodontal disease and arrhythmia. In line with this result, a case-control study by Sridhar et al [10] found that coronary heart disease did not exacerbate the destruction of periodontal tissue. The inconsistencies between these studies might have been due to differences in study design, the adjustments made for confounding variables, and other methodological details.…”
Section: Introductionsupporting
confidence: 67%
“…HolmPedersen et al [9] investigated the correlations among dental caries, periodontal disease, and cardiac arrhythmia in community-dwelling elderly individuals who were aged 80 or older and showed that there was no association between periodontal disease and arrhythmia. In line with this result, a case-control study by Sridhar et al [10] found that coronary heart disease did not exacerbate the destruction of periodontal tissue. The inconsistencies between these studies might have been due to differences in study design, the adjustments made for confounding variables, and other methodological details.…”
Section: Introductionsupporting
confidence: 67%
“…However, this relationship was not observed between the mild form of periodontal disease as well as the risk of hyperlipidemia in patients with severe chronic periodontitis; risk of hyperlipidemia was 30% higher than those of the normal subjects (19,20). Observations of Sridhar et al indicated that TG levels were not correlated with attachment loss increase in patients with periodontitis (5).…”
Section: Discussionmentioning
confidence: 68%
“…In periodontal disease, cytokines secretion increase is observed, which results in impaired fat metabolism and hyperlipidemia. On the other hand, hyperlipidemia is known as a risk factor for cardiovascular diseases (5,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes show that both periodontal tissue breakdown (PD) and level of inflammation (bPP) impinge on the lipid serum level. The results of scientific research on LDL-C concentration in the blood of patients with CVD depending on the state of periodontal tissues are ambiguous [16,17]. However, the majority of reports on patients without cardiovascular burden indicate an impact of periodontitis on lipid disorders expressed by elevated levels of LDL-C, TC and TG, and a reduced level of HDL-C [3,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%